Effects of maturation on lower limb neuromuscular asymmetries in elite youth tennis players - Madruga-Parera, M.; Romero-Rodriguez, D.; Bishop, C.; Reyes Beltran-Valls, M.; Latinjak, A. T.; Beato, M.; Fort-Vanmeerhaeghe, A. (Sports, 2019)
Neuromuscular asymmetries have been previously associated with reduced performance. Similarly, maturation has shown that youth athletes may experience a loss of motor control, which could also lead to compromised physical performance. The present study aimed to evaluate and quantify the level of asymmetry among chronological and maturational groups. Forty-one youth tennis players performed the single leg countermovement jump (SLCMJ), star excursion balance test (SEBT) and a change of direction speed (CODS) test. Differences were found between the strongest and weakest limbs across all tests (p < 0.001), and also for SEBT in the posteromedial direction (p = 0.02), SEBT composite score (p < 0.01) in maturation groups, and for SEBT posterolateral direction (p = 0.03) and SEBT composite score (p = 0.01) in chronological groups. The SLCMJ showed the largest inter-limb asymmetries for the circa peak height velocity (PHV) group (19.31 ± 12.19%) and under-14 (U14) group (17.55 ± 9.90%). Chronological and maturation groups followed similar trends for inter-limb asymmetries, but the biological index showed larger asymmetry scores in the jumping test at PHV compared to that found in the chronological group (U14). These results show that inter-limb differences may be heightened during PHV. Practitioners can use this information to inform the decision-making process when prescribing training interventions in youth tennis players.